PENGARUH PEMBERIAN AKUPRESURE TITIK LI-4 (TITIK HEGU) TERHADAP DISMINORE PADA REMAJA PUTRI DI SMA 15 PEKANBARU - Putri Indra Gandi; Hulfa Ahadian Haryanti; Ulfa Nadia Nurul Firdaus; Riwayati Malika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Dysmenorrhea occurs when there is an excessive increase in prostaglandin levels in the endometrium during the proliferative phase leading to the secretory phase, which can result in contractions of the myometrium, causing ischemia that is followed by a decrease in progesterone levels at the end of the luteal phase. This results in pain in the uterine muscles before, during, and after menstruation. This condition can last for 2 days or more during each month’s menstrual period. Management of dysmenorrhea pain can be approached through non-pharmacological therapy, specifically by applying pressure to the Li4 meridian point (Hegu Point). The aim of this research is to determine the effect of Li4 acupressure (Hegu Point) on dysmenorrhea pain in adolescents with dysmenorrhea.. This research method is quantitative with a one-group pretest-posttest experimental design conducted at SMA 15 Pekanbaru. The population consists of all female students of SMA 15 Pekanbaru with Purposive sampling technique. The sample for this study includes female students experiencing pain. Data collection was carried out by distributing pretest and posttest questionnaires using the Numeric Rating Scale (NRS). The LI-4 acupressure was administered 20 times over three consecutive days by a therapist, after which the respondents continued during menstruation. Data analysis was conducted using univariate and bivariate methods. The results showed a decrease in dysmenorrhea pain, with a pre-treatment average of 2.67 and a standard deviation of 0.687, while after three consecutive days of acupressure treatment, the average intensity of dysmenorrhea pain was 1.19 with a standard deviation of 0.552. The results of the Wilcoxon test showed a decrease in the average intensity of dysmenorrhea pain on day 1 of 0.22, on day 2 of 0.43, and on day 3 of 0.83, with a P value of 0.00, which means that the application of acupressure at point LI 4 (Hegu) has an effect on dysmenorrhea in teenage.Keywords: Acupressure, Pain Intensity, Dysmenorrhea, Teenage